Port Governance and Bureaucratic Challenges: A Literature Review of Regulatory Reform in the Indonesian Maritime Sector - Juliana Eka Pratiwi; Selvira Aryani (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2026)
Port governance in Indonesia remains a critical issue within maritime sector reform due to institutional fragmentation, overlapping authority, bureaucratic complexity, and uneven implementation of regulatory policies. As an archipelagic country, Indonesia depends heavily on efficient port systems to support logistics connectivity, investment, inter-island trade, and maritime competitiveness. This study aims to examine how regulatory reform shapes Indonesian port governance and to identify the bureaucratic challenges that affect the implementation of reform in the maritime sector. Using a qualitative descriptive literature review approach, this article analyzes secondary data from peer-reviewed journal articles, policy documents, institutional reports, and relevant academic publications. The data were examined through qualitative content analysis by identifying key themes related to port governance, regulatory reform, bureaucratic coordination, digital integration, institutional capacity, and stakeholder collaboration. The findings indicate that regulatory reform has encouraged modernization in port management, service integration, and digital transformation; however, its effectiveness remains limited by fragmented institutional mandates, procedural rigidity, weak inter-agency coordination, and uneven bureaucratic capacity across ports. The study also finds that digitalization can improve transparency and efficiency, but only when supported by regulatory coherence, organizational readiness, and integrated information systems. This article concludes that Indonesian port reform should be understood not merely as legal or infrastructural modernization, but as a broader governance transformation requiring regulatory harmonization, bureaucratic simplification, institutional coordination, stakeholder participation, and adaptive policy learning to strengthen national maritime competitiveness.